The investigator - Sandford, John, 1944 February 23- (New York : G.P. Putnam's Sons, 2022)
Letty Davenport, the brilliant and tenacious adopted daughter of Lucas Davenport, takes the investigative reins. By age twenty-four, Letty Davenport has seen more action and uncovered more secrets than many law enforcement professionals. Now a recent Stanford grad with a master's in economics, she's restless and bored in a desk job for U.S. Senator Colles. Letty's ready to quit, but her skills have impressed Colles, and he offers her a carrot: feet-on-the-ground investigative work, in conjunction with the Department of Homeland Security.
Keywords: Davenport, Letty -- (Fictitious character) -- Fiction; Davenport, Lucas -- (Fictitious character) -- Fiction; United States. -- Department of Homeland Security -- Fiction; Criminal investigation -- Fiction; Theft -- Fiction; Thrillers (Fiction); Detective and mystery fiction